Question

( 2 A-B=left[begin{array}{rrr}6 & -6 & 0 -4 & 2 & 1end{array}right], A-2 B cdotleft[begin{array}{rrr}3 & 2 & 8 -2 & 1 & -7end{array}right] )
( B=frac{1}{3}left[begin{array}{ccc}0 & -10 & -16 0 & 0 & 15end{array}right] )
( B=left[begin{array}{ccc}0 & -10 / 3 & -16 / 3 0 & 0 & 5end{array}right] )
Substitult in first
[
2 A=left[begin{array}{ccc}6 & -6 & 0 -4 & 2end{array}right]+left[begin{array}{ccc}0 & -10 & 3 & -16 0 & 0 & 5end{array}right]
]
( left.A=frac{1}{2}left[begin{array}{cc}6 & -28 / 3 -4 & 2end{array}right]-16 mid 3right} )
( A=left[begin{array}{rrr}3 & -14 / 3 & -8 / 3 -2 & 1 & 3end{array}right] )

# Find matrices A and B, if 2A-B -6 07 1-4 2 1 0 [3 2 87 and A-2B= 1-21 -7 |

Solution